Dissemination of oil draining machine technology for MSMEs Cassava Chips Maju Jaya Singosari, Malang Regency - Yepy Komaril Sofi'i; Sudarman Sudarman (Universitas Muhammadiyah Magelang, 2022)
MSMEs Cassava Chips Maju Jaya in the oil draining process still use conventional methods. This causes the oil cannot be drained optimally with a shelf life of only 1-2 weeks. The implementation of this program aims to disseminate oil draining machine technology. This program is carried out with the stages of partner observation, manufacturing and testing of oil draining machines, and training and mentoring in the use of oil draining machines. The dimensions of the oil draining machine are 600 mm x 430 mm x 560 mm, with a capacity of 10 kg per draining procedure. The motor used is an AC electric motor with a power of HP. The oil drainer's outside and interior bodies are constructed from 304 stainless steel plate and vortexed stainless steel. This helps to make the oil draining procedure easier and quicker. The oil draining process is done by inserting cassava chips into the machine for 15 minutes until the oil content is reduced. From the test, the shelf life of the product is increased to 2 months. This can make a positive contribution to the quality of MSME Maju Jaya products.